How Therapists-in-Training Experience and Manage Their Therapy-Related Self-Doubts: A Thematic Analysis - Natale, Tessa (Université d'Ottawa | University of Ottawa, 2025)
One of the key elements of effective counselling is the mental health of the counsellor.Research has shown that the efficacy of counselling is diminished if the therapist presentsanxiety in their role or lacks confidence in their mastery of counselling skills (Lambert, 1989;Royse-Roskowski, 2010; Tsai, 2015). Therapist factors also contribute to approximately 9% ofthe outcome variance (cf. Wampold & Imel, 2015), which is higher than the variance attributedto the actual treatment used. Therapist feelings of incompetence (FOI) or self-doubt have beenidentified as a potential factor that may impact the therapeutic outcome (Theriault & Gazzola,2009, 2010). Yet, the experience of self-doubt from the therapist-in-training perspectiverequires further investigation. This stage of development is characterized as one that presentsmany challenges through its exposure to novel experiences and changes in identity(Morrissette, 1996; Rønnestad & Skovholt, 2003). In researching self-doubt from theirperspective, I am aiming to reduce its potential negative impacts on client welfare, as well as tobetter support budding therapists and their development. Three research questions haveguided my research: (1) What are the sources of self-doubt in therapists-in-training? (2) How isself-doubt experienced both before, during, and after sessions with clients? And (3) How dotherapists-in-training cope with self-doubt? Using inductive qualitative research methodology,8 therapists-in-training in Ontario participated in semi-structured, 60–75-minute interviews todiscuss their experience of self-doubt. The data was analyzed using Braun and Clark’s (2006,2012) six-step thematic analysis to uncover themes shared by participants to contribute to thecurrent body of literature on the topic. The findings from research question (1) yielded thecreation of 5 main themes and 16 sub-themes and are located within the fourth chapter of thecurrent thesis, which consists of a manuscript prepared to be submitted for publication. Thefindings from research question (2) led to the emergence of 3 main themes and 8 sub-themesand are found within chapter five, along with the findings from research question (3), which ledto the development of 4 main themes and 12 sub-themes.
Keywords: Qualitative research; Thematic analysis; Self-doubt; Psychotherapy; Therapist-in-training